PENGARUH PERMAINAN TRADISIONAL LOMPAT KARUNG TERHADAP PENINGAKATAN DAYA LEDAK OTOT TUNGKAI - Hidayat, Refdi; Aluwis; Putra, Riwaldi (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
This research is motivated by the low level of explosive power of the leg muscles of students, This is because many students who practice jumping often play around and are not serious in following the learning, especially in traditional game materials. This study aims to see the effect of the traditional game of sack jumping on increasing the explosive power of the leg muscles of students. This research is a quasi-experimental method study continued by looking at the contribution of variable X to variable Y. The population in this study were students of SMP Islam Kepenuhan totaling 75 students using the Total Sampling sampling technique with a sample size of 25 students. This research was conducted using the traditional game method of sack jumping and taking the Standing Broad Jump test. Data analysis used is the normality test analysis with the lilliefors method, homogeneity and hypothesis testing using the t test. The results of the hypothesis testing analysis from measurements carried out on the pre-test and post-test with the same test, namely Standing Broad Jump, obtained t count 3.381> t table 1.711 which means Ho is rejected and Ha is accepted. The traditional sack jumping game has a significant effect on the explosive power of the leg muscles of students at Kepenuhan Islamic Middle School.